Biografie nauczycieli śląskich. Źródła i stan badań - Sapia-Drewniak, Eleonora (Acta Universitatis Nicolai Copernici Pedagogika, 2016)
The work of teachers from the 19th century until contemporary times, significant for Upper Silesia as it is, has not found a broader reflection in biographical elaborations to date. Historiography has devoted much attention mainly to Polish-German antagonisms, showing the role of “heaven-sent” individuals: cultural and political activists of the day, who were, in many cases, teachers by profession, that form of their activity being merely mentioned. A similar situation occurred after the end of the Second World War – the work of teachers was not the subject of deepened scholarly analyses either. Resource materials – both relating to the didactic work of Silesian teachers in the 19th and the 20th centuries are fairly rich, although they are dispersed and must be looked for in different Polish and German archives. This void in the Silesian historiography needs to be filled with historians’ of education undertaking to develop biographical studies on teachers of elementary, vocational and secondary schools.